2010
DOI: 10.14741/ijcet/spl.2.2014.113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quarter Car Model of Active Pneumatic Suspensions using Mass Flow Control for a Small Car

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The simulation findings demonstrated that independent stiffness and the ride height control tuning can enable suspension that is more adaptable design for striking a better balance between a numerous conflicting requirements and obstacles was presented by Yin et al [2]. The active pneumatic suspension with control strategy for a commercially manufactured small car which based on mass flow control with two different control strategies were presented, the first model mass flow to the air source has to be based on the differences of velocity between excitation and sprung mass and the mass flow rate in the second model is the sinusoidal function of the stimulation frequency from the base were presented by Razdan et al [3].…”
Section: Introductionmentioning
confidence: 99%
“…The simulation findings demonstrated that independent stiffness and the ride height control tuning can enable suspension that is more adaptable design for striking a better balance between a numerous conflicting requirements and obstacles was presented by Yin et al [2]. The active pneumatic suspension with control strategy for a commercially manufactured small car which based on mass flow control with two different control strategies were presented, the first model mass flow to the air source has to be based on the differences of velocity between excitation and sprung mass and the mass flow rate in the second model is the sinusoidal function of the stimulation frequency from the base were presented by Razdan et al [3].…”
Section: Introductionmentioning
confidence: 99%